Extraction and Determination of Hormones in the Edible Bird's Nest - Ma, Fucui; Liu, Daicheng (Asian Journal of Chemistry, 2011)
Six kinds of hormones in two types of edible bird's nests, the white nest built by Aerodramus fuciphagus and the black nest built by A. maximus, were detected for the first time. These six kinds of hormones are testosterone, estradiol, progesterone, luteinizing hormone, follicle-stimulating hormone and prolactin. The ultrasonically assisted extraction methods, the optimal solvent used and the optimal ratio of of solvent to sample (v/w) were determined. The contents of each of these six kind of hormones were significantly different in the white and black nests as determined by full-automated microparticle chemiluminescent immunoassay. The determination of these hormones in the edible bird's nests may explain part of the effects of the edible bird's nest and may serve as an useful analytical technique for differentiating between white and black nest or the grades of the edible bird's nest products and it may be a useful method to determine adulteration.